Light chain immunofluorescence in various nephropathies - Megha S Uppin; Aruna K Prayaga; B H Srinivas; Ram Rapur; Madhav Desai; K V Dakshina Murthy (Indian Journal of Pathology and Microbiology, 2011)
Context: Light chain immunofluoresence (IF) in renal biopsy is routinely used in the diagnosis of light chain deposition disease (LCDD), amyloidosis and cast nephropathy. Light chain predominance has also been reported in certain glomerulopathies like IgA nephropathy. However, pathogenesis of this pattern of deposition in various glomerulopathies is uncertain. Aim: To discuss the pathogenesis and utility of light chain IF in nephropathies. Setting and Design: Retrospective study. Materials and Methods: The pattern of light chain IF and light microscopic diagnosis in 306 cases of various nephropathies was reviewed. Direct IF was done in all these cases with commercial fluorescence (Fluoresciene Isothiocynate ) conjugated polyclonal rabbit anti-human antisera against IgM, IgG, IgA, C3, C1q, kappa and lambda light chains. Results: Light chain deposits were seen in 240 (78.43%) cases. In IgA nephropathy, lupus nephritis and post-infectious glomerulonephritis (PIGN), lambda positivity was more as compared to kappa. Light chain deposits in LCDD and membranous nephropathy were more kappa type. The IF pattern in amyloidosis was not consistent. Conclusion: The pathogenesis of light chain predominance in glomerulopathies is not clear and it depends on isoelectric point and size of the immune complex. Light chain IF should be performed routinely in all the renal biopsies.